2022
DOI: 10.1039/d1sc06071f
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent suppression of Aβ aggregation and NLRP3 inflammasome activation for treating Alzheimer's disease

Abstract: Bifunctional molecule BPBA inhibits Aβ aggregation and NLRP3 inflammasome activation, thereby decreasing ROS and IL-1β in vitro and vivo; it synergistically prevents Alzheimer's disease via alleviating Aβ neurotoxicity and reducing neuroinflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…There is a significant link between NLRP inflammasome and the pathogenesis of Alzheimer’s disease [ 59 , 60 ]. Aβ plaques not only induce oxidative stress and damage neurons, but also activate NLRP3 inflammasomes further releasing IL-1β to trigger neuroinflammation in patients with Alzheimer’s disease [ 61 ]. In neurons, NLRP1 inflammasome levels increase by approximately 25–30 fold in the patients with Alzheimer’s disease [ 62 ].…”
Section: Roles Of Nlrp Inflammasome In Neuropsychiatric Disordersmentioning
confidence: 99%
“…There is a significant link between NLRP inflammasome and the pathogenesis of Alzheimer’s disease [ 59 , 60 ]. Aβ plaques not only induce oxidative stress and damage neurons, but also activate NLRP3 inflammasomes further releasing IL-1β to trigger neuroinflammation in patients with Alzheimer’s disease [ 61 ]. In neurons, NLRP1 inflammasome levels increase by approximately 25–30 fold in the patients with Alzheimer’s disease [ 62 ].…”
Section: Roles Of Nlrp Inflammasome In Neuropsychiatric Disordersmentioning
confidence: 99%
“…AD is crucially related to Aβ plaques, which not only induce oxidative stress but also activate the NLRP3 inflammasome, releasing inflammatory cytokine IL-1β to trigger neuroinflammation. 32 In addition, tau phosphorylation can result in NFT, which is an important histopathological feature of AD. 2 Our previous studies showed that GMs had anti-oxidative, anti-inflammatory and neuroprotective activities, suggesting that GMs could exhibit potential anti-AD effects.…”
Section: Resultsmentioning
confidence: 99%
“…Benzoic acid derivatives present in garlic shells can be combined with other compounds to synergistically activate the PPAR signaling pathway or inactivate the phospholipase D signaling pathway to exert an anti-T2DM effect ( 86 ). In addition, the bifunctional molecule BPBA synthesized using benzoic acid can target Aβ and inhibit neuroinflammation, which plays a role in AD ( 87 ). To the best of our knowledge, this study is the first to identify the potential role of acetamidobenzoic acid in the pathogenesis of obesity–T2DM–AD, thus laying a foundation for the subsequent development of new drugs.…”
Section: Discussionmentioning
confidence: 99%